Evaluation of Tigecycline Susceptibility by Disk Diffusion, E-test and Broth Microdilution Methods in 30 Multidrug Resistant or Extreme Drug Resistant Acinetobacter Isolates (Annals of Medical Research, 2021)
None
Keywords: Acinetobacter spp; Multi-Drug-Resistance; Tigecycline; E Test; Broth Microdilution.